“IMPLIKASI HUKUM PENGANGKATAN TENAGA HONORER MENJADI CALON PEGAWAI NEGERI SIPIL” - Satriya Nugraha (Yuriska: Jurnal Ilmiah Hukum, 2017)
In the Employment Law is not found that the Government may appoint civil servants Candidate (employess) derived from Honorary Workers but then with Government Regulation No. 48 Year 2005 About Appointment of Honorary Workers Being employess has set a policy that the Government may appoint honorary be employess and then amended by Government Regulation No. 43 of 2007 On Amendment of Government Regulation No. 48 Year 2005 concerning the appointment of Honorary Workers Being employess. This study aims to assess the presence of Honorary Workers in the perspective of Employment Law and Legal Implications Power Honorary appointment into employess. This type of research is normative and descriptive analytical study the rules or norms of positive law, relating to the Government's policy to raise the Honorary Workers be employess. The results of this study found that the appointment of Honorary Workers become employess more viscous aspects of public policy rather than juridical aspects. But public policy is then given a legal basis in the form of Government Regulation. Legal implications of the appointment of Honorary be employess conflict between Employment Law with Government Regulations governing, so that under the principles of law should be a higher Regulations beat / disregard the underlying Regulation and this may mean that the implications of the appointment of Honorary Workers into the civil servant is not valid in terms of Legal Aspects